INTERNAL STEM ANATOMY OF SIX BROMUS SPECIES GROWN IN DUHOK PROVINCE, KURDISTAN REGION. IRAQ - Abdulrahman, Haliz A. (Science Journal of University of Zakho, 2023)
The stems of six species of Bromus (B. scoparius L., B. lanceolatus Roth., B. sterilis L., B. madritensis L., B. squarrosus L. and B. danthoniae Trin.) which belongs to Poaceae family grown in Duhok province, Kurdistan region, Iraq were examined anatomically. The samples of Bromus species have been collected from Duhok city in spring 2022. The research was carried out at Biology department, Faculty of science, University of Zakho. The study aims to distinguish between the anatomical differences among the Bromus species since they share phenotypic traits that make it difficult to distinguish them apart. The samples were fixed in formalin- acetic-acid alcohol (FAA) and cross sections were prepared, examined using compound light microscope and photographed at different power. The highest number and measures of the vascular bundles, thicknesses of cuticle, epidermis, hypodermis, and the diameters of the minor and major vascular bundles (stele) were recorded in the B. danthoniae. while, the highest dimeters of metaxylem and cross section of stem were appeared in B. scoparius and B. sterilis, respectively. On the other hand, the lowest number and measures of the above-mentioned features were fluctuated among the Bromus sterilis, B. lanceolatus, B. madritensis. The cross sections indicated that there were valuable differences in both qualitative and quantitative values of the anatomical features among the species.
Keywords: Annual Grass; Stem Anatomy; Stele; Vascular Bundle; Metaxylem